The mind in another place: my life as a scholar - Johnson, Luke Timothy (William B. Eerdmans Publishing Company, 2022)
"A memoir by Luke Timothy Johnson in which Johnson reflects on the life experiences that made him a scholar and on the general requirements of scholarship"--